The Interplay of Nutriepigenomics, Personalized Nutrition and Clinical Practice in Managing Food Allergy - Adli Ali (MDPI AG, 2021)
Food allergy in children has been a common issue due to the challenges of prescribing personalized nutrition with a lack of nutriepigenomics data. This has indeed further influenced clinical practice for appropriate management. While allergen avoidance is still the main principle in food allergy management, we require more information to advance the science behind nutrition, genes, and the immune system. Many researchers have highlighted the importance of personalized nutrition but there is a lack of data on how the decision is made. Thus, this review highlights the relationship among these key players in identifying the solution to the clinical management of food allergy with current nutriepigenomics data. The discussion integrates various inputs, including clinical assessments, biomarkers, and epigenetic information pertaining to food allergy, to curate a holistic and personalized approach to food allergy management in particular.